Al-Biruni's views on the discovery of the spherical earth - Mohd Ibrahim, Azhar; Shuriye, Abdi Omar (IIUM Press, 2011)
The objective of this chapter is to explain the concept of spherical earth and the data used is collected from reliable sources. The technique of Eratosthenes was used to measure the circumference of the earth, 200 years before Al Biruni. However, this chapter investigates the method used by AI-Biruni to find the earth's circumference and this was the most precise calculation of earth's circumference during the medieval period. The chapter also explores the mathematical solutions that were provided by AI-Biruni to determine the circumference and radius of the earth. Hence, the significance of this chapter is to present AI-Biruni's concept of spherical earth